Teaching Foreign Language Listening Skill to Students of Secondary Schools - Mamedova Madina Ashuralievna; Rizayeva Firangiz Fakhritdinovna (Genius Journals, 2023)
This article discusses the process of teaching listening skill of foreign language to students of secondary schools. As you know, in order to ensure communicative competence and free speech activity of students, skills such as reading, writing, speaking, and listening should be developed. Listening, an integral, significant part of human speech activity, has been and still remains without due attention: listening training is still among the poorly developed problems of methodology and is not fully embodied in the content of teaching a foreign language.
Keywords: speech skill; communicative competence; podcast